2008
DOI: 10.1016/j.jmb.2007.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Orientation of T4 Lysozyme Bound to the Small Heat Shock Protein α-Crystallin

Abstract: We have determined the structural changes that accompany the formation of a stable complex between a destabilized mutant of T4 lysozyme (T4L) and the small heat shock protein alpha-crystallin. Using pairs of fluorescence or spin label probes to fingerprint the T4L tertiary fold, we demonstrate that binding disrupts tertiary packing in the two domains as well as across the active-site cleft. Furthermore, increased distances between i and i+4 residues of helices support a model in which the bound structure is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…A recent model of sHSP chaperone function suggests that sHSP oligomers exist in two forms with differential activity: a low affinity state and a high affinity state (3,20). We propose here that, in the case of the ␣-crystallins, these two forms correspond to oligomers with dimeric and monomeric substructure, respectively (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…A recent model of sHSP chaperone function suggests that sHSP oligomers exist in two forms with differential activity: a low affinity state and a high affinity state (3,20). We propose here that, in the case of the ␣-crystallins, these two forms correspond to oligomers with dimeric and monomeric substructure, respectively (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…2A) of the Hsp16.5-WT/T4L sample show that this fraction consists of clustered Hsp16.5 particles. Previous studies suggested that low affinity bound T4L are likely to be on the outer shell of the oligomer exposed to solvent (29). These molecules can then mediate the clustering of Hsp16.5 particles.…”
Section: Binding Of Hsp165-tr and Hsp165-p1 To Destabilized T4l Doementioning
confidence: 98%
“…Interpretation of these experiments is intrinsically difficult and hindered by the heterogeneity of the substrate proteins under the non-equilibrium conditions typical of aggregation-based assays. To overcome these limitations, Claxton et al (29) used a spectroscopic approach to characterize the structure of T4L bound to ␣-crystallin. They demonstrated that native tertiary contacts are disrupted and secondary structure elements are unfolded supporting the contention that the stably bound T4L conformation is extensively unfolded.…”
mentioning
confidence: 99%
“…Recent studies by Mchaourab and colleagues on the interaction of destabilized T4 lysozyme mutants with sHsps have led to a proposed mechanism of sHsp chaperone action in which the equilibrium between the folding and unfolding of the target protein (T4 lysozyme) is coupled to the equilibrium between the dissociated (dimeric) and oligomeric states of α-crystallin [42][43][44]. α-Crystallin binds T4 lysozyme in two modes with high and low affinity.…”
Section: Crystallins and The Eye Lensmentioning
confidence: 99%
“…α-Crystallin binds T4 lysozyme in two modes with high and low affinity. In this model, the dimeric form of the sHsp is the activated state which recognizes and binds to the destabilized target protein [44].…”
Section: Crystallins and The Eye Lensmentioning
confidence: 99%